Flipping the Script in the New Normal: Investigating the Efficacy of Flip Learning for English Language Learning in University Settings - Ni Putu Ade Resmayani; Sri Wahyuningsih (International Journal of Instructions and Language Studies, 2023)
This research aims to illustrate the capacity of flipped learning to revitalize the classroom atmosphere and promote increased levels of student engagement and enthusiasm within the contemporary post-pandemic educational setting. Employing a mixed-methods approach, it includes surveys and interviews with 100 students from Indonesian universities. The study aims to uncover the benefits and challenges of implementing flip learning in non-English department English classrooms and explore how students perceive this approach. The intervention involved delivering pre-recorded lectures and activities for students to complete before class, followed by in-person activities and discussions to reinforce learning. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data underwent thematic analysis. The results indicate that implementing flip learning for non-English department students at the university level offers several benefits, including enhanced student engagement and motivation, improved short-term learning outcomes, increased student-teacher interaction, more opportunities for problem-solving practice, collaborative learning experiences, and flexible learning pace. However, challenges like increased workload, group activities, limited technology access, and teacher adaptation to new teaching methods may arise. Despite these challenges, the benefits of flip learning outweigh the drawbacks, making it a viable approach for non-English department university students studying English. These findings lay the groundwork for future research to address workload management, effective collaboration, technology accessibility, teacher support, long-term learning assessment, and implementing flipped learning in diverse educational contexts.